Estudio comparativo del número de yemas en la poda de la vid (Vitis labrusca) sobre los rendimientos de la variedad borgoña negra (Isabella) en San Antonio de Cumbaza San Martín - Vela Paredes, Willian (1998)
With the purpose to find out the adequate number of buds for the pruning of vine (vitis labrusca) and its influence on the yiel in the variety Black Burgundy (Isabella) has been realised this work between March and June 1 998 in the district of San Antonio de Cumbaza, in the San Martin Region located at latitude 06°25 South, longitude 76°25 West at 789 metres above sea level. The installation of the experiment has been realized on a plantation established since four years. The design used for the experiment was the Complete Random Block (DBCR) with four repetitions, five treatments and one witness. Six numbers or lengths of buds in the pruning of vine has been studies in the following way: T1 (Pruning at 1 bud), T2 (Pruning at 2 buds - witness), T3 (Pruning at 3 buds), T4 (Pruning at 4 buds), T5 (Pruning at 5 buds) and T6 (Pruning at 6 buds) Without taking into account the numbre of plants within the experimental field, applying a total of 24 treatments or experimental unities. In the studies treatments were applied a growth regulator called Hydrogenated Cyanamid (Dormex) 3% in order to unify and activate the budding after pruning. In order to control the evolution of the vine, five applications has been realized f 7, 31, 38, 51 and 65 days after the pruning on the whole plantation using the chemical product Metaloxil and Mancozeb (Hieloxil) with the dose of 60 gr/20 It. water mixed with and adherent (Agridex) in the dose of 10 ml/20 It. water. These applications avoided attacks of Mildiu (Plasmofora viticola), one of the most frequent diseases in vine cultivation of the region. The evaluated parameters were: Days between pruning and budding, Number of buds per shoot, number of flower buds per bunch, Days between pruning and flowering, Number of bunches per buds, number of coagulated grains, Days between pruning and harvest, number of bunches per treatment, kilograms of grapes per treatment, size of the bunches and yield. With the obtained yields has been realized the economic analysis, relating cost and benefit of each treatment. The best results relative to the study of the buds in the paining of vine and its influence on the yield has been obtained with treatment T5 (Pruning at 5 buds) with a yield per hectare of 7 522,00 kg. of fresh grapes and with a net benefit of 4 012.74 US $ per hectare.